Shiroro Hydro Electricity Dam and Happiness of Host Community: An Evaluation Using Propensity Score Matching Analysis - Ewugi, Musa Salihu; Karim, Mohd Zaini Abd; Abdul-Hakim, Roslan (International Journal of Economics and Financial Issues, 2016)
The objective of the study is to examine the impact of Shiroro Hydro Electricity Dam (SHED) on the happiness of the host community. In order to achieve this aim, Propensity Score Matching techniques is employed, which involved two research points – Shiroro community where the dam is installed (treatment group) and Gurara community with similar river but without dam (control group). The findings revealed that, due to installed dam, the host community is less happiness by 59 percent. Therefore, in the spirit of ‘give and take”, and for the fact that the community is an agrarian community, the study recommends that government should put up structure of flood forecast in place for early warning signals to minimise flood pains. In conclusion, it is argued that understanding and operating on the plat form that all man’s actions are aimed at achieving happiness will improve global happiness. Keywords: Happiness, Host-community, Shiroro JEL Classification: C6